2019
DOI: 10.1158/0008-5472.can-18-1888
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Domains in Gastrointestinal Stromal Tumor Regulate KIT Expression and Are Targetable by BET Bromodomain Inhibition

Abstract: Gastrointestinal stromal tumor (GIST) is a mesenchymal neoplasm characterized by activating mutations in the related receptor tyrosine kinases KIT and PDGFRA. GIST relies on expression of these unamplified receptor tyrosine kinase (RTK) genes through a large enhancer domain, resulting in high expression levels of the oncogene required for tumor growth. Although kinase inhibition is an effective therapy for many patients with GIST, disease progression from kinase-resistant mutations is common and no other effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The same pattern of activation of distinct BET-dependent super enhancers was also reported in chronic lymphocytic leukemia [82]. Enhancers driving the transcription of receptor tyrosine kinases that play a fundamental role in gastrointestinal stromal tumor have also shown dependence on BET family members [83].…”
Section: Epigenetic Modulatorssupporting
confidence: 58%
“…The same pattern of activation of distinct BET-dependent super enhancers was also reported in chronic lymphocytic leukemia [82]. Enhancers driving the transcription of receptor tyrosine kinases that play a fundamental role in gastrointestinal stromal tumor have also shown dependence on BET family members [83].…”
Section: Epigenetic Modulatorssupporting
confidence: 58%
“…The same pattern of activation of distinct BET-dependent super enhancers was also reported in chronic lymphocytic leukemia [89]. Enhancers driving the transcription of receptor tyrosine kinases that play a fundamental role in gastrointestinal stromal tumors have also shown dependence on BET family members [90].…”
Section: Perturbing Enhancer Activity By Therapeutic Agents and Inmentioning
confidence: 69%
“…The pathogenesis of NF-1-associated GISTs has not been established. Several studies have confirmed that NF-1-associated GISTs are different from sporadic GISTs with respect to clinicopathologic characteristics, and KIT and PDGFRA gene mutations[1,5]. Moreover, the age and location of onset differ.…”
Section: Discussionmentioning
confidence: 99%
“…The data revealed that none of the six tumors from the two patients had a KIT exon 9, 11, 13, or 17, PDGFRA exon 12 or 18, or BRAFV600E mutation, which typically occurs in sporadic GISTs. It is reported most of the GISTs associated with NF-1 are well differentiated histologically, small in size, exhibit low proliferative activity, are often benign, and have a good prognosis[1,4]. Surgical resection of GIST is still the preferred method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation